2017
DOI: 10.1111/andr.12405
|View full text |Cite
|
Sign up to set email alerts
|

Andrology of male‐to‐female transsexuals: influence of cross‐sex hormone therapy on testicular function

Abstract: Patients with gender dysphoria are offered cross-sex hormone therapy and sex reassignment surgery to achieve the transition between the sex assigned at birth and gender identity. According to international guidelines, cross-sex hormone therapy in trans-women should lead to a psychologically and physiologically healthy body with feminized serum hormone levels, resulting in suppression of spermatogenesis. However, in a recently published multi-center study, we discovered a high proportion of patients with male s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 61 publications
1
48
0
5
Order By: Relevance
“…Furthermore, our results from juveniles and the transfemale testes strongly suggest that States 0 and 1 are indeed reserve (undifferentiated, quiescent, or slow-cycling) spermatogonia that persist from infancy to adulthood even in the absence/suppression of T. For example, in the T-suppressed testes, while spermatogenesis is severely impaired, we observed a population of spermatogonia with the same transcriptional profile as the State 0-1 population identified in untreated adult testes (Guo et al, 2018). This likely accounts for the ability of spermatogonia in some transfemales to resume gametogenesis when T suppression is halted (Kohn et al, 2017;Schneider et al, 2017).…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, our results from juveniles and the transfemale testes strongly suggest that States 0 and 1 are indeed reserve (undifferentiated, quiescent, or slow-cycling) spermatogonia that persist from infancy to adulthood even in the absence/suppression of T. For example, in the T-suppressed testes, while spermatogenesis is severely impaired, we observed a population of spermatogonia with the same transcriptional profile as the State 0-1 population identified in untreated adult testes (Guo et al, 2018). This likely accounts for the ability of spermatogonia in some transfemales to resume gametogenesis when T suppression is halted (Kohn et al, 2017;Schneider et al, 2017).…”
Section: Discussionmentioning
confidence: 57%
“…20 The few available studies of transgender women on estrogen therapy rely on small sample sizes (n = 1 to n = 11) and heterogeneous treatment protocols (low or high dose estrogen, estrogen + anti-androgens, oral vs transdermal) resulting in incomplete and often conflicting results. 21 Prolonged estrogen exposure has been reported to result in atrophy and absent or impaired spermatogenesis, 22,23 while normal spermatogenic activity and complete reversibility have also been reported. [24][25][26] One recent study reported heterogeneous results among 108 transgender women presenting for gender-affirming surgery after gender-affirming hormone treatment ranging from normal spermatogenesis (24%) to tubular shadows/atrophy (1.85%).…”
Section: Effects Of Estrogen Therapy On the Testiclementioning
confidence: 99%
“…A transwoman who has had full gender affirmation surgery (including testes removal) will have very low testosterone levels below 1 nmol/L 14. These transwomen will have much less opportunity for a performance advantage in comparison to elite cis-women athletes.…”
Section: Terminologymentioning
confidence: 99%